1998
DOI: 10.1046/j.1365-294x.1998.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the freshwater fish, Mogurnda adspersa, in streams of northeastern Queensland, Australia: evidence for altered drainage patterns

Abstract: A phylogeographic survey was used to elucidate the relative roles of historical processes and contemporary gene flow in structuring the genetic pattern observed with Mogurnda adspersa. This species of freshwater fish is found in the rivers and streams of the northeastern highlands of Queensland, Australia. Specifically, this project focused on populations in the Tully and Herbert Rivers in the Atherton Tablelands. Sequence analysis indicated that three distinct clades exist in the headwaters of the Tully River… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 22 publications
1
116
0
Order By: Relevance
“…In a previous phylogenetic study conducted at a broader spatial scale (de Bruyn et al, 2004), it was suggested that Pleistocene drainage basins that linked sites on the Sunda Shelf that are today geographically isolated, may have acted as conduits for gene-flow among some populations of M. rosenbergii. Similar studies on freshwater fish indicate the important role that ancient drainage basins have played in shaping the distribution of molecular variation in freshwater organisms (Hurwood and Hughes, 1998;Waters et al, 2001;Kotlik et al, 2004 and others). This ancient drainage basin hypothesis goes some way to describing the close relationship among populations observed here, particularly for sites d-h (ie southern Thai-Malay Peninsula and Sth.…”
Section: Discussionmentioning
confidence: 64%
“…In a previous phylogenetic study conducted at a broader spatial scale (de Bruyn et al, 2004), it was suggested that Pleistocene drainage basins that linked sites on the Sunda Shelf that are today geographically isolated, may have acted as conduits for gene-flow among some populations of M. rosenbergii. Similar studies on freshwater fish indicate the important role that ancient drainage basins have played in shaping the distribution of molecular variation in freshwater organisms (Hurwood and Hughes, 1998;Waters et al, 2001;Kotlik et al, 2004 and others). This ancient drainage basin hypothesis goes some way to describing the close relationship among populations observed here, particularly for sites d-h (ie southern Thai-Malay Peninsula and Sth.…”
Section: Discussionmentioning
confidence: 64%
“…The reference individual used for heteroduplexing was from the Stony Creek site. The specific methodology used is outlined in Hurwood and Hughes (1998). The optimal conditions identified for the TGGE analysis consisted of a gradient of 27-451C for which the samples were run at 300 V for 2.75 h. The resulting banding pattern was visualised with silver staining (DIAGEN).…”
Section: Allozymesmentioning
confidence: 99%
“…The Stream Hierarchy Model predicts that populations from the same stream will be more similar to one another than to populations from different streams in the same subcatchment, and populations from different subcatchments in the same drainage will be more similar to one another than to those from other drainages (Meffe and Vrijenhoek, 1988). Although genetic variation in many aquatic species does appear to fit the stream hierarchy model (eg the freshwater prawn Macrobrachium australiense, Cook et al, 2002; the pacific blue-eye Pseudomugil signifera, , there seem to be as many instances where this is not the case (eg the zebra shrimp Caridina zebra, Hurwood and Hughes, 2001; the purple-spotted gudgeon Mogurnda mogurnda, Hurwood and Hughes, 1998; the empire gudgeon Hypseleotris compressa, . One explanation for these anomalies is that drainage rearrangements have occurred in recent geological time, and current genetic patterns reflect the structure of past, rather than present stream architecture .…”
Section: Introductionmentioning
confidence: 99%